1993
DOI: 10.1136/adc.68.5_spec_no.566
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone treatment in preterm infants at risk for bronchopulmonary dysplasia.

Abstract: A randomised double blind placebo controlled study was conducted to determine whether a one week course of dexamethasone could reduce the severity of bronchopulmonary dysplasia in preterm infants without compromising their adrenal function. Forty one infants with a mean birth weight of 880 g and a gestational age of 27 weeks who were ventilator dependent at 10 days of age were enrolled. At the age of 28 days pulmonary outcome was significantly better in the girls treated with dexamethasone but not in all infan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 16 publications
0
51
0
1
Order By: Relevance
“…Steroids may have a somewhat different mechanism of action in CLD or early CLD from that detected in prenatal treatment. Several studies have failed to show a sustained beneficial effect of DEX in preterm infants when the treatment was discontinued (3,5,18). It has been speculated that respiratory failure seen after discontinuation of DEX is related to the return of the inflammatory state (5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Steroids may have a somewhat different mechanism of action in CLD or early CLD from that detected in prenatal treatment. Several studies have failed to show a sustained beneficial effect of DEX in preterm infants when the treatment was discontinued (3,5,18). It has been speculated that respiratory failure seen after discontinuation of DEX is related to the return of the inflammatory state (5).…”
Section: Discussionmentioning
confidence: 99%
“…According to current evidence, DEX treatment of preterm ventilator-dependent infants with threatened CLD decreases the requirements of ventilatory support (3,5,7,8,16,18) and improves pulmonary mechanics (4-6). DEX treatment has decreased the concentrations of albumin in lung effluent (5,15,16), suggesting decreased endothelial and epithelial permeability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19,20 Other prospective trials have also reported a high incidence of other adverse effects, including an increase in nosocomial sepsis, meningitis, and hyperglycemia 21,22 ; hypertriglyceridemia; increased free fatty acid levels 23 ; increased protein catabolism and poorer somatic growth [24][25][26] ; and pituitary-adrenal suppression, 27 which can last for 1 month after therapy. 28,29 None of the published trials evaluating PNSs were powered to evaluate long-term follow-up. A number of reports, many describing follow-up studies of infants enrolled in randomized, controlled trials of PNSs to prevent or ameliorate bronchopulmonary dysplasia (BPD), noted that such use was associated with a significantly increased occurrence of neurodevelopmental impairment, especially if the risk of the development of CLD was Ͻ35% in the control infants.…”
Section: Authorsmentioning
confidence: 99%